The diachrony of definiteness in north Germanic - Skrzypek, Dominika; Piotrowska, Alicja; Jaworski, Rafał (Brill's studies in historical linguistics, 2021)
"This book is an account of the rise of definite and indefinite articles in Danish, Swedish and Icelandic, as documented in a choice of extant texts from 1200-1550. These three North Germanic languages show different development patterns in the rise of articles, despite the common origin, but each reveals interdependencies between the two processes. The matter is approached from both a quantitative and a qualitative perspective. The statistical analysis provides an improved overview on article grammaticalization, focusing on the factors at the basis of such process. The in-depth qualitative analysis of longer text passages places the crucial stage of the definite article grammaticalization with the so-called indirect anaphoric reference"--